More than a game : the computer game as fictional form - Atkins, Barry (Manchester University Press ; Distributed exclusively in the USA by Plagrave, 2003)
This is the first academic work dedicated to the study of computer games in terms of the stories they tell and the manner of their telling. It considers the computer game as a new and emerging mode of contemporary storytelling in a fashion that is accessible and readable.